Validasi Kuesioner Baru Menilai Pengetahuan dan Persepsi tentang Kombinasi antara Pengobatan Herbal dan Konvensional - I. N. FARIDAH; M.N. C. PUTRI; D. A. PERWITASARI (Fakultas Farmasi Universitas Pancasila, 2017)
Indonesia is a country which has great potential of herbal medicine, although combination between herbal and conventional medicine can be benefi cial or harmful. Knowledge and perceptions about that combination are needed to achieve the best treatment eff ect. To validate a new instrument assessing knowledge and perceptions of patients about combination between herbal and conventional medicine. This study used cross sectional study which was conducted in some of pharmacy in Yogyakarta. Inclusion criterias of the subject were people who visited to the pharmacy with ages above 18 years old and below 65 years old, also had used the combination of herbal and conventional medicine for minimal a month to achieve the same goal of treatment. Items of the questionnaire were developedby existing literatures and added some new items. The content validity had been conducted by some experts. Analysis statistic with bivariate correlations was used to determine the validity and reliability of the questionnaire. Subjects who met the inclusion criteria were 30 people, which are consisted of 15 ofhealthy people and the rest are people who use the combination. In the domain of knowledge, there are 16 valid questions over 19 questions. Reliability had been calculated by 16 questions and it was reliable (cronbach alpha 0.863). In the perception domain, there were 8 valid questions. The reliability showed that the questions were reliable (cronbach alpha 0.862). There are 3 invalid questions because all of the answer is similar. Our study provides that this new questionnaire was valid and reliable to a ssessknowledge and perception of the patient who use combination of herbal and conventional medicine.